2006
DOI: 10.1111/j.1600-0625.2006.00439b.x
|View full text |Cite
|
Sign up to set email alerts
|

The vitamin D endocrine system of human sebocytes

Abstract: Locally produced vitamin D metabolites are of high importance for growth regulation in various tissues. Using real‐time PCR, we have characterized expression of key components of the vitamin D system vitamin D receptor (VDR), vitamin D‐25‐hydroxylase (25OHase), 25‐hydroxyvitamin D−1 α‐hydroxylase (1αOHase), and 1,25‐dihydroxyvitamin D‐24‐hydroxylase (24OHase) in the SZ95 human sebaceous gland cell line. Incubation of SZ95 cells with 1,25‐dihydroxyvitamin D resulted in a dose‐dependent suppression of cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…In recent years, it has been shown that epidermal keratinocytes (Fig. 4) and other cell types including Langerhans cells, dermal dendritic cells, macrophages, melanocytes, prostate, lung and colon cancer cells, contain the enzymatic machinery needed to produce 1,25(OH) 2 D 3 (91,92). 1,25(OH) 2 D 3 exerts its effects via binding to a specific nuclear vitamin D receptor (VDR), a ligand‐dependent transcription factor that belongs to the superfamily of steroid/thyroid hormone/retinoid nuclear receptors and that recognizes specific DNA sequences named vitamin D response elements.…”
Section: Vitamin D and Human Sebocytesmentioning
confidence: 99%
“…In recent years, it has been shown that epidermal keratinocytes (Fig. 4) and other cell types including Langerhans cells, dermal dendritic cells, macrophages, melanocytes, prostate, lung and colon cancer cells, contain the enzymatic machinery needed to produce 1,25(OH) 2 D 3 (91,92). 1,25(OH) 2 D 3 exerts its effects via binding to a specific nuclear vitamin D receptor (VDR), a ligand‐dependent transcription factor that belongs to the superfamily of steroid/thyroid hormone/retinoid nuclear receptors and that recognizes specific DNA sequences named vitamin D response elements.…”
Section: Vitamin D and Human Sebocytesmentioning
confidence: 99%
“…It has been reported that incubation of the SZ95 human sebaceous gland cell line with 1,25(OH) 2 D 3 results in a dose‐dependent suppression of cell proliferation (7). Using real‐time PCR, it was demonstrated that key components of the vitamin D system (VDR, 25OHase, 1 α OHase, and 24OHase) are strongly expressed in SZ95 cells (7).…”
Section: The Sebaceous Gland: a Target For Biologically Active Vitamimentioning
confidence: 99%
“…It has been reported that incubation of the SZ95 human sebaceous gland cell line with 1,25(OH) 2 D 3 results in a dose‐dependent suppression of cell proliferation (7). Using real‐time PCR, it was demonstrated that key components of the vitamin D system (VDR, 25OHase, 1 α OHase, and 24OHase) are strongly expressed in SZ95 cells (7). It has been concluded that local synthesis or metabolism of vitamin D metabolites may be of importance for growth regulation and various other cellular functions in sebaceous glands and that sebaceous glands represent promising targets for therapy with vitamin D analogues or for pharmacological modulation of calcitriol synthesis/metabolism (7).…”
Section: The Sebaceous Gland: a Target For Biologically Active Vitamimentioning
confidence: 99%
See 2 more Smart Citations